Kompetensi Kepribadian Islami Kepala Sekolah: Analisis Kitab Syakhsiyatu Al-Rasul Karya Nizar Abadzah - Janah, Tufatul; Bahruddin, Ending (Tawazun: Jurnal Pendidikan Islam, 2021)
The principal's personality competence is the first of the five competency standards that every school principal must possess. Some aspects of personality competencies possessed by school principals aim to improve the system and quality in the world of education. So the principal needs a model in leadership that reflects the personality of the perfect leader. Therefore, this study will examine the book Syakhsiyatu Al-Rasul by Nizar Abadzah which will describe how the personality of the Prophet Muhammad as a role model for humans in leading. So that it can be used as a guide for school principals in carrying out their leadership. The focus of the problem in this study is to formulate the Islamic personality competencies of school principals. This study uses a qualitative approach to the type of library research (library research). The data sources used are primary data sources and secondary data sources. Data analysis used content analysis, namely by analyzing data on the personality competencies of school principals according to Nizar Abadzah in the book of Syakhsiyatun Rasul. It can be formulated that the principal's Islamic personal competence is the personal ability of the principal that reflects a personality that has good morals, has the basic character of the leadership of the Prophet, by integrating the workings of aqliyah and nafsiyah based on Islamic aqidah which gives birth to actions in accordance with the example of the Prophet, upholding the truth and putting full trust in Allah. by maintaining self-sanctity in carrying out the mandate of his leadership. Abstrak Kompetensi kepribadian kepala sekolah merupakan kompetensi pertama dari lima standar kompetensi yang harus dimiliki oleh setiap kepala sekolah. Beberapa aspek kompetensi kepribadian yang dimiliki oleh kepala sekolah bertujuan agar dapat memperbaiki system dan mutu dalam dunia pendidikan. Maka kepala sekolah memerlukan model dalam kepemimpinan yang mencerminkan kepribadian pemimpin yang sempurna. Maka dari itu, penelitian ini akan menelaah kitab Syakhsiyatu Al-Rasul karya Nizar Abadzah yang akan mendeskripsikan bagaimana kepribadian Rasulullah e sebagai suri teladan manusia dalam memimpin. Sehingga mampu dijadikan sebagai pedoman kepala sekolah dalam menjalankan kepemimpinannya. Fokus masalah dalam penelitian ini adalah merumuskan kompetensi kepribadian Islami kepala sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian pustaka (library Research). Sumber data yang digunakan adalah sumber data primer dan sumber data sekunder. Analisis data digunakan analisis isi (content analysis) yaitu dengan cara menganalisis data tentang kompetensi kepribadian kepala sekolah menurut Nizar Abadzah dalam kitab Syakhsiyatun Rasul. Dapat dirumuskan kompetensi kepribadian Islami kepala adalah kemampuan personal kepala sekolah yang mencerminkan kepribadian yang berakhlak karimah, berkarakter dasar kepemimpinan Rasulullah, dengan mengintegrasikan cara kerja aqliyah dan nafsiyah berdasarkan aqidah Islam yang melahirkan perbuatan sesuai dengan teladan Rasulullah, memegang teguh kebenaran dan bertawakal penuh kepada Allah, dengan menjaga kesucian diri dalam menjalankan amanah kepemimpinannya.